Near‐total mandibular reconstruction following osteoradionecrosis with double scapula tip free flap: A case report. Issue 1 (17th August 2021) - Barton, Blair M.; Blumberg, Jeffrey M.; Patel, Samip N.
Abstract: Near‐total mandibular reconstruction poses many challenges to reconstructive surgeons. The purpose of this article is to present a challenging case in a patient with osteoradionecrosis of the mandible requiring a near‐total mandibular reconstruction using bilateral scapula tip free tissue reconstruction. A 68‐year‐old African–American male with a history of T2N0M0 squamous cell carcinoma of the tonsil presented with advanced stage osteoradionecrosis of the mandible. Reconstruction was planned using 3D Systems (Denver, CO), mandibular osteotomies were planned inferior to the sigmoid notch on the ascending rami. Neither fibula flap was amenable for harvesting due to poor vasculature of the patient's lower extremities, and bilateral scapula tip free flaps were subsequently planned. The post‐operative course was complicated by venous congestion in the right scapula flap which required revision to the venous anastomosis on POD 1. The patient had intraoral breakdown that required debridement in the operating room and application of a cellular matrix. The patient fully recovered from the acute surgery and was discharged home without a tracheostomy. At the last follow up visit, the patient was taking 100% of diet peroral and had no signs of oral incompetence, mental projection was satisfactory, and the ability to verbally communicate was unimpaired. We report a complex case of near‐total mandibular reconstruction using simultaneous bilateral scapula tip free flaps. While we do not advocate simultaneous bilateral scapula tip free flaps as the standard of care for large mandibulectomy defects, it may be considered for patients in which traditional osseous free flaps are not available.